1862 Or. Spec. Laws 9, An Act to Incorporate the City of Albany, § 6. - (:unkn) unknown (General Publisher, 1862)
[To] regulate the storage of gun powder and other combustible materials, and the use of candles, lamps and other lights in shops, stables and other places[.]
--
Keywords: GUN POWDER STORAGE